Services Liberalization in Preferential Trade Arrangements : The Case of Kenya - Balistreri, Edward J.; Tarr, David G. (2012)
Given the growing importance of commitments to foreign investors in services in regional trade agreements, it is important to develop applied general equilibrium models to assess the impacts of liberalization of barriers to multinational service providers. This paper develops a 55 sector applied general equilibrium model of Kenya with foreign direct investment and Dixit-Stiglitz productivity effects from additional varieties of imperfectly competitive goods or services, and uses the model to assess its regional and multilateral trade options, focusing on commitments to foreign investors in services. To assess the sensitivity of the results to parameter values, the model is executed 30,000 times, and results are reported as confidence intervals of the sample distributions. The analysis reveals that a 50 percent preferential reduction in the ad valorem equivalents of barriers in all business services by Kenya with its African partners would be somewhat beneficial for Kenya. If a preferential agreement with African partners is combined with an agreement with the European Union, the gains would more than triple the gains of an Africa only agreement. Multilateral reduction of services barriers, however, would yield gains about 12 times the gains of an agreement with the Africa region alone. These results suggest that preferential liberalization in the region is a valuable first step, but wider liberalization, with larger partners and liberal rules of origin or multilaterally, will yield much larger gains due to providing access to a much wider set of services providers. The largest gains would come from domestic regulatory reform in services, as this would almost triple the gains of multilateral liberalization.